PERHITUNGAN PELAT BETON BERTULANG DENGAN BALOK – BALOK BERDASARKAN METODE PERENCANAAN LANGSUNG DAN METODE PORTAL EKIVALEN PADA PROYEK PEMBANGUNAN GEDUNG DISPERINDAG KOTA SAMARINDA - SUDRAJAT, DEDE (KURVA S JURNAL MAHASISWA, 2014)
Two way slab is a plate system with the principle of the beam position which is right under the plate that sustains the power plate..The aim of this project is to determine the results of the calculation of the concrete slab system with the direct method and equivalent method portal at the same equivalence ratio of moment magnitude and deviation.In this calculations, Concrete slab planned by using the direct method and the method of planning portal equivalent. Planning methods should be a minimum direct discharge of duties continuous spans in each direction, the panel must be rectangular with a ratio between the length of the span short span measured between the axis to the axis of the pedestal is not more than two. Method equivalent portal is an approach of the real order that is the framework of a three-dimensional portal into the framework of a two-dimensional portal in the field of the column. This approach requires the existence of a relationship between the columns with column plate is transfer the bending strength of the plate to end the meeting with the column component.The results of this planning is Concrete saf or thick plate dimensions (15 cm); to use the flexural reinforcement diameter f 12; shear reinforcement using ordinary reinforcement using reinforcement diameter f 12, obtained the advantage that in terms of artistic look better, and easy to set up as required at the completion of the end.